Analisis Performa Pemain Bali United Football Academy U-8 Berbasis Small-Sided Games: Perspektif Teknik Dasar dan Agresivitas - Gede Ngurah Damar Widhi Satya; Wasti Danardani; Ketut Chandra Adinata Kusuma (Jurnal Inovasi Olahraga, 2026)
This study aims to analyze the performance of Bali United Football Academy U-8 players in small-sided games, focusing on basic passing and dribbling techniques, first touch, and hostile and instrumental aggressiveness observed during the implementation of small-sided games. This study employs a quantitative descriptive method using direct observation via video. The sample in this study consisted of 6 U-8 players with different playing positions who had participated in training sessions for 6 months at the Bali United Football Academy. The findings indicate that the success rates for passing, dribbling, and first touch among the players fall into the “good” category, with a passing success rate of 73.74%, a dribbling success rate of 78.26%, and a first-touch success rate of 78.57%. Regarding the findings on hostile and instrumental aggression exhibited by the players, there were a total of 51 instances of instrumental aggression, while hostile aggression occurred 19 times. These results indicate that players more frequently engage in aggressive actions with positive intentions during the game. This study found that the small-sided games method can be used to assess passing, dribbling, first touch performance, as well as hostile and instrumental aggression among players at the Bali United Football Academy U-8. Future research could introduce modifications to the small-sided games study, such as increasing the number of players, the duration of training sessions, and the field size, as well as analyzing more basic techniques or soccer actions that emerge during the implementation of small-sided games.